PERANCANGAN CULTURAL MAPPING SEBAGAI BRANDING UMKM DESA DERMASUCI, KABUPATEN TEGAL - Ratna, Maharani Patria; Saputri, Lenggahing; Wijayanti, Cici (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2023)
Community service has become a valuable approach in preserving and promoting the cultural potential and local identity of a region. Dermasuci Village, Tegal Regency has a diversity of cultures and rich traditions that have carved alluring traces, radiated charm, and become valuable assets to develop the local economy. With the spirit to develop and improve the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Dermasuci Village, Cultural Mapping design has been planned as a creative and strategic initiative. The exploration of cultural values and local potential will be the foundation for creating authentic and evocative branding, while strengthening the existence and attractiveness of local MSME products. Through Cultural Mapping, it is expected that more cultural aspects will be explored and optimally utilized. This activity was carried out by conducting field surveys and interviews with relevant parties. After that, the data collected is made into a module which will later become a cultural-themed archive.